Mediterraneo e migrazioni: La donna e il mare nel teatro spagnolo contemporaneo (TEST Ticontre. Theory Text Translation, 2022)
Study of the female figure and her relationship with the sea in contemporary Spanish drama on the theme of migration. Within this line of late Hispanic theatre, the connection between woman and sea has become a metaphor for the dead, a reflection of a tragic reality. The investigation focuses on three works that are particularly significant for the very personal aesthetics of the authors and for the originality of the thematic treatment developed in each of them: Angélica Liddell’s Y los peces salieron a combatir contra los hombres, Antonia Bueno’s Aulidi (hijo mío) and Juana Escabias’ Babel.